The C-CAP Process: A Comprehensive Approach to Community Resource Mapping - Mowle, Amy; Klepac, B.; Riley, T.; Craike, M. (2025)
Introduction: Place-based systems change approaches are gaining popularity to address the complex problems associated with locational disadvantage. An important stage of place-based systems change involves understanding the context that surrounds (re)produces a target problem. Community resource mapping can be used to establish the context and identify the strengths of a community that might be leveraged through systems change efforts. Approaches to community resource mapping draw on a range of philosophical assumptions and methodological frameworks. However, comprehensive, practical guidance for researchers and practitioners to conduct community resource mapping is scarce. Method: Drawing on the learnings from a literature review, scoping workshops, and reflective practice sessions, we developed a flexible, methodologically robust process called the Contextualize, Collect, Analyze, and Present (C-CAP) process: a four-phase approach to preparing for, conducting, and reporting on community resource mapping. The C-CAP process was co-developed by researchers and practitioners and was tested and refined in two different communities. Results: The C-CAP process provides robust guidance for conducting and reporting on a community resource mapping project. The C-CAP process can be applied by public health practitioners and researchers and adapted for use across different communities, problems, and target groups. We encourage others guided by differing theoretical perspectives to apply C-CAP and share the learnings. Conclusion: Application of the C-CAP process has the potential to improve the comparability and comprehensiveness of findings from community resource mapping projects and avoids duplication of effort by reducing the need to design new processes for each new community resource mapping activity.